Association between vitamin D and C-reactive protein level in post-COVID recovery period - Chakraborty, Sisir; Sinha, Sanchayan; Ghosh Sengupta, Soumita; Satwika Sinha; Chakraborty, Indranil (Asian Journal of Medical Sciences, 2023)
Background: Severe acute respiratory distress syndrome coronavirus 2 pandemic shows a spectrum of symptoms and complications which are variably dependent on individual’s immune status. Vitamin D deficiency, often preexisting, causes poor prognosis in the post-COVID recovery phase of the survivors characterized by increased C-reactive protein (CRP) and decreased D-dimer levels. Aims and Objectives: The aims of this study were to find any correlation exists between vitamin D level and inflammatory marker CRP and D-dimer in post-COVID period. Materials and Methods: Seventy post-COVID recovery patients from the follow-up medicine outpatient department of College of Medicine and Sagore Dutta Hospital were tested for vitamin D, D-dimer, and serum CRP levels. Results: CRP levels of patients with lower vitamin D level (<20 ng/ml) were significantly higher (P<0.001) than the patients with higher vitamin D level. The D-dimer levels of vitamin D deficient group found to be significantly higher than the other group. There is statistically significant negative correlation found between CRP and vitamin D level and significant positive correlation has been found between D-dimer and vitamin D (P<0.001). Conclusion: Vitamin D may have an important role in recovery stage of COVID patients.